Torsion of wandering spleen treated by laparoscopic splenopexy: A case report. (2019) - Awan, Mariyem; Gallego, Jose Luis; Al Hamadi, Annett; Vinod, Vijay Chander
Highlights: Wandering spleen. Laparoscopic splenopexy. Torsion of splenic pedicle. Abstract: Introduction: A wandering spleen is a mobile spleen as a result of deficient splenic peritoneal ligaments and elongation of its vascular pedicle. It is a rare entity affecting mainly young adults commonly females and children, presenting as an asymptomatic abdominal mass or abdominal discomfort due to torsion and de-torsion of the pedicle. Presentation of case: We report a 35-year-old female presented with intermittent colicky abdominal pain that worsened in severity over three weeks. Diagnostic laparoscopy showed torsion of spleen without infarction. Detorsion and Splenopexy in an extra-peritoneal pouch was performed. Post operatively, the patient recovered well and was healthy at two months follow up. Discussion: A wandering spleen is either congenital or acquired. The condition results in a long vascular pedicle, which predispose to the torsion resulting in a partial or complete infarct of the spleen. Laparoscopic approach is the preferred technique and de-torsion of the splenic pedicle and splenopexy is a reasonable surgical option, when there is no evidence of infarction of the spleen. Conclusion: The diagnosis of wandering spleen is very rare and extremely difficult to establish and is clinically nonspecific. An early diagnosis and surgical care are required for preserving the spleen. Additional imaging examinations can help establish a diagnosis.